2006
DOI: 10.1002/aoc.1144
|View full text |Cite
|
Sign up to set email alerts
|

Novel photoswitching dithienylethenes with ferrocene units

Abstract: Two novel dithienylethenes with ferrocene units were synthesized by Wittig reaction. The structure of 2a has been established by X-ray diffraction studies. They could reversibly interconvert between two thermally stable forms, an open and a closed one, using light of different wavelengths as triggers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The key starting material, ethynylferrocene, was synthesized by adaptation of a literature method. 25,65,66 The NMR spectra were recorded on a Bruker AM-400 spectrometer in CDCl 3 . The (1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key starting material, ethynylferrocene, was synthesized by adaptation of a literature method. 25,65,66 The NMR spectra were recorded on a Bruker AM-400 spectrometer in CDCl 3 . The (1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The key starting material for the bis(ferrocenylethynyl) compounds, ethynylferrocene (1), was prepared in good yield by adaptation of a literature procedure by Luo et al 65 in preference to other reported synthetic methods for this compound. 25,66 The dibromo/diiodo heteroaromatic precursors for 3−7 were prepared as reported previously. 40,67,68,75 The syntheses of 2− The IR spectra of the bis(ferrocenylethynyl) complexes show a single, sharp ν(CC) in the 2200−2010 cm −1 range, characteristic of other ethynylferrocenyls 42,43,76 containing aromatic and heteroaromatic spacer groups.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Photochromic compounds have gained much attention due to their potential applications in switching devices and optical memory media . By taking this into account, Yin et al synthesized a compound carrying dithienylethenes as photochromic moiety . The isomerization of dithienylethenes can be altered from ring open to ring close form and vice versa upon irradiation of suitable wavelength.…”
Section: Ferrocene‐based Electro and Photo Responsive Materialsmentioning
confidence: 99%
“…The oxidation of dithienylethenes usually occurs at high potential so this drawback was tried to solve in this work by the addition of ferrocene with dithienylethenes which provided ring open and close process at a low potential. When dithienylethenes moiety was combined with ferrocene, the resulting compound showed excellent thermal stability and photochromic properties which can be applied for memory device application (Scheme ) . Zuckerman et al .…”
Section: Ferrocene‐based Electro and Photo Responsive Materialsmentioning
confidence: 99%
“…Photo‐responsive polymers are macromolecules that change their properties due to light‐induced isomerization or cleavage of specific functional groups along the backbone or the side chains 45. 46 The responses consist of changes in refractive index,47 dielectric constant,48 redox potential,49 geometrical structure,50 and luminescence properties 51. Photo‐responsive polymers find extensive applications in reversible optical storage, polymer viscosity control, photomechanical transduction and actuation, bioactivity switching of proteins, tissue engineering, and drug delivery 5255…”
Section: Dual‐stimuli Responsivenessmentioning
confidence: 99%